Asesmen Diagnostik Dalam Pembelajaran Menulis Teks Tanggapan Di SMPN 3 Merangin - Leola, Sherly; Febriani, Sandra Tri; Rustam, Rustam; Nazurty, Nazurty (Jayapangus Press, 2024)
The ability to write response texts is a crucial aspect of Indonesian language learning at the junior high school level. Minimum Competency Assessment (MCA) is an important instrument to measure this skill. This study aims to evaluate the response text writing ability of grade VIII students of SMPN 3 Merangin using the AKM and identify effective learning strategies. With a qualitative descriptive approach and a case study of 30 students, data were collected through the AKM test and analyzed qualitatively. The results showed significant variations in students' writing literacy skills. A total of 15% of students were in the excellent category, demonstrating the ability to understand, analyze, and compose structured, logical, and critical responses. Meanwhile, 45% of students were in the good category, able to understand and analyze the text well, and compose adequate responses. Furthermore, 35% of students were in the fair category, showing a general understanding of the text but may struggle with in-depth analysis or structured responses. Finally, 5% of students were in the poor category, with writing literacy skills that need to be significantly improved, especially in comprehending, analyzing, and composing clear and coherent responses. The findings serve as a reference for designing more effective learning strategies, especially in literacy development and response text writing. This study provides a comprehensive picture of the ability to write response texts of grade VIII students at SMPN 3 Merangin. The findings can serve as a reference in designing more effective learning strategies, especially in developing literacy skills and writing response texts. AKM is proven to be effective as an assessment tool for writing response texts at the junior high school level and schools are expected to utilize the results of this study to design lessons that focus on strengthening writing literacy.